2000
DOI: 10.1021/jp002947t
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Quenching by Oxygen of 9,10-Dimethylanthracene in Liquid and Supercritical Carbon Dioxide

Abstract: The contribution of diffusion to the fluorescence quenching by oxygen of 9,10-dimethylanthracene (DMEA) in liquid CO2 and supercritical CO2 (SCF CO2) at pressures up to 60 MPa was investigated. For comparison, the fluorescence quenching by CBr4 of DMEA was also investigated. The apparent activation volume of the quenching rate constant, k q, was 8 ± 1 and 10 ± 3 cm3/mol for DMEA/O2, and 42 ± 7 and 400 ± 90 cm3/mol for DMEA/CBr4 in liquid CO2 (25 °C, 10 MPa) and SCF CO2 (35 °C, 8.5 MPa), respectively. For DMEA/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
54
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(60 citation statements)
references
References 32 publications
6
54
0
Order By: Relevance
“…1,2 It was demonstrated for many molecules that k S q was approximately a diffusion-controlled value whereas the rate constant (k T q ) for oxygen quenching of the lowest excited triplet state (T 1 ) was roughly 1/9 of k S q , and this observation was explained reasonably in terms of the difference of spin-multiplicity in the energy transfer from the two excited states to oxygen. As shown in previous papers, [3][4][5][6][7] k S q of anthracenes substituted at the meso-position depends significantly on the electron-donating character of the substituent and is fairly smaller than a diffusion-controlled limit for the derivatives possessing electron-withdrawing substituents such as 9,10dicyanoanthracene (DCNA), CNA and DCLA.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…1,2 It was demonstrated for many molecules that k S q was approximately a diffusion-controlled value whereas the rate constant (k T q ) for oxygen quenching of the lowest excited triplet state (T 1 ) was roughly 1/9 of k S q , and this observation was explained reasonably in terms of the difference of spin-multiplicity in the energy transfer from the two excited states to oxygen. As shown in previous papers, [3][4][5][6][7] k S q of anthracenes substituted at the meso-position depends significantly on the electron-donating character of the substituent and is fairly smaller than a diffusion-controlled limit for the derivatives possessing electron-withdrawing substituents such as 9,10dicyanoanthracene (DCNA), CNA and DCLA.…”
Section: Introductionmentioning
confidence: 65%
“…The values of F 0 T for solutions containing no oxygen are determined by eqn. (5) from the ratio of U s to total heat released (U t ),…”
Section: Methodsmentioning
confidence: 99%
“…Another derivative of anthracene i.e. 9,10-dimethyl anthracene (DMA) reacts almost irreversibly with 1 O 2 in various organic and aqueous medium with a significantly high rate constant (6.8 × 10 7 -5.7 × 10 10 M −1 S −1 ) with the result of producing non fluorescent 9,10-endoperoxide [21][22][23][24]. Elim Albiter et.al reported a facile photosensitized oxidation of 9,10 demethylanthracene with 1 O 2 in presence of safranin O/ silica composite as a heterogeneous photosensitizer [21] in which they reported that oxidation rate does not depend on surface of the composite rather depend only the initial concentration of DMA, light intensity and the amount of composite formed.…”
Section: 10-dimethyl Anthracene (Dma)mentioning
confidence: 99%
“…22,23 In previous publications, 25,26 the pressure effect on the fluorescence quenching of pyrene by polybromoethanes, Q, with wide quenching ability in liquid solutions has been studied and successfully interpreted on the basis of a kinetic model, which involves the exciplex, (MQ)*, via the encounter complex, 1 (M*Q) en , formed between the lowest excited singlet state, 1 M*, and Q. This model was successfully applied to the fluorescence quenching of DMEA by oxygen (8.5-40.0 MPa) and CBr 4 (8.5-60.0 MPa) 27 and of DCNA by oxygen (8.0-60.0 MPa) 28 in SCF CO 2 at 35 C as well as in liquid CO 2 (10.0-60.0 MPa) at 25 C, and the fluorescence quenching for these systems in SCF CO 2 was shown to be interpreted in the same framework as that in liquid CO 2 , indicating no contribution of local composition enhancement to the quenching in the pressure range examined.…”
Section: Introductionmentioning
confidence: 99%